Organic-inorganic hybrid and composite materials
The organic inorganic hybrid material with controlled QD cohesion addresses aggregation issues, enhancing dispersion and maintaining material properties.
Patent Information
- Application Number
- JP2021000470
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-05
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2041-01-05
AI Technical Summary
Quantum dots (QD) tend to aggregate in composite materials, leading to cohesion issues.
An organic inorganic hybrid material represented by the average composition formula (1) is used, which includes specific organic functional groups and crosslinked oxygen, controlling QD cohesion and improving dispersion.
The hybrid material effectively suppresses QD aggregation, ensuring improved dispersion and preventing cracks, while maintaining transparency and heat resistance.
Smart Images

Figure 0007625418000001 
Figure 0007625418000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to organic-inorganic hybrid and composite materials. [Background technology]
[0002] A method for producing an inorganic particle composite resin is disclosed in Patent Document 1. In this production method, the surfaces of inorganic particles are modified with a surface modifier, and then the inorganic particles are dispersed in a resin. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-210385 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, technology using quantum dots (QDs) has been attracting attention. A composite material containing a matrix composition and QDs dispersed in the composition is considered as a material using QDs. However, QDs tend to aggregate in the composition.
[0005] In one aspect of the present disclosure, it is preferable to provide organic-inorganic hybrid and composite materials that can suppress the aggregation of QDs. [Means for solving the problem]
[0006] One aspect of the present disclosure is an organic-inorganic hybrid material represented by the average composition formula (1). Formula (1) SiR 1 a R 2 b R 3 c (OX) d (O 1 / 2 ) e (R in Equation (1)1 is an organic functional group that contains an unsaturated carbon bond and does not contain an aromatic ring. 2 is an organic functional group that contains an aromatic ring and does not contain an unsaturated carbon bond outside the aromatic ring. 3 is an organic functional group that does not contain an unsaturated carbon bond. X in formula (1) is hydrogen or an alkyl group. O in formula (1) 1 / 2 is a bridging oxygen. In formula (1), a is a numerical value of 0.04 or more and 0.26 or less. In formula (1), b is a numerical value of 0.13 or more. In formula (1), c is a numerical value of 0.09 or more. In formula (1), d is a numerical value of 0 or more. In formula (1), e is a numerical value of 0 or more. The sum of a, b, and c is a numerical value of 1.04 or more and 1.49 or less. The sum of a, b, c, d, and e is 4.) The organic-inorganic hybrid material according to one aspect of the present disclosure can be used to produce a composite material, for example. The composite material includes an organic-inorganic hybrid material and QDs dispersed in the organic-inorganic hybrid material. In the composite material, the QDs are less likely to aggregate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] Exemplary embodiments of the present disclosure will now be described. 1. Organic-inorganic hybrid materials The organic-inorganic hybrid material of the present disclosure is represented by the average composition formula (1).
[0008] Formula (1) SiR 1 a R 2 b R 3 c (OX) d (O 1 / 2 ) e The sum of a, b, c, d, and e is 4. 1 / 2is a bridging oxygen. In formula (1), e is a numerical value of 0 or more. For example, e is a numerical value greater than 0. The organic-inorganic hybrid material of the present disclosure is, for example, a polymer formed by polymerizing an organic silane compound. The main chain of the polymer is bonded by a SiO bond.
[0009] R in formula (1) 1 R is an organic functional group that contains an unsaturated carbon bond and does not contain an aromatic ring. Examples of aromatic rings include a benzene ring and a naphthalene ring. 1 R has the function of increasing flexible organic bonds through addition polymerization. 1 A part or all of R may be in a state of addition polymerization. 1 By including this, cracks are less likely to occur.
[0010] In formula (1), a is a value between 0.04 and 0.26. When a is 0.04 or more, cracks are less likely to occur in the organic-inorganic hybrid material. When a is 0.26 or less, QD aggregation can be further suppressed when a composite material is produced using the organic-inorganic hybrid material of the present disclosure. The reason why QD aggregation can be further suppressed can be presumed as follows. When a is 0.26 or less, the crosslink density does not become excessively high in the organic-inorganic hybrid material. As a result, the dispersibility of QD in the organic-inorganic hybrid material is improved.
[0011] R 1 Examples of the alkyl group include one or more groups selected from the group consisting of a vinyl group, an acrylic group, a methacrylic group, and an allyl group. R in formula (1) 2is an organic functional group that contains an aromatic ring and does not contain an unsaturated carbon bond other than the aromatic ring. Examples of aromatic rings include a benzene ring and a naphthalene ring. In formula (1), b is a value of 0.13 or more. When a composite material is produced using the organic-inorganic hybrid material of the present disclosure, the aggregation of QDs can be further suppressed by making b 0.13 or more. The reason why the aggregation of QDs can be further suppressed can be presumed as follows. When b is 0.13 or more, the compatibility between the organic chain on the surface of the QD and the organic-inorganic hybrid material is improved. As a result, the dispersibility of QDs is improved.
[0012] R 2 Examples of the alkyl group include one or more selected from the group consisting of a phenyl group, a 4-methoxyphenyl group, and a benzyl group. R in formula (1) 3 R is an organic functional group that does not contain an unsaturated carbon bond. 3 For example, R consists of only alkyl groups. 3 does not contain an aromatic ring, for example. In formula (1), c is a numerical value of 0.09 or more. When c is 0.09 or more, the reactivity of the organic-inorganic hybrid material is increased, and the organic-inorganic hybrid material is easily cured.
[0013] R 3 Examples of the alkyl group include one or more selected from the group consisting of a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a cyclopentyl group, a cyclohexyl group, a hexyl group, an n-octyl group, an isooctyl group, a decyl group, a dodecyl group, a hexadecyl group, an n-octadecyl group, and an octadecyl group.
[0014] In formula (1), X is hydrogen or an alkyl group. Examples of the alkyl group include one or more groups selected from the group consisting of a methyl group, an ethyl group, a 1-propyl group, a 2-propyl group, and the like. Formula (1) is represented by the formula (OX) d In formula (1), d is a numerical value equal to or greater than 0. The organic-inorganic hybrid material of the present disclosure can be easily synthesized by a sol-gel method or the like using raw materials such as an organosilane compound containing (OX).
[0015] The sum of a, b, and c (hereinafter referred to as the sum of abc) is 1.04 or more and 1.49 or less. When the sum of abc is 1.04 or more, the aggregation of QDs can be further suppressed when a composite material is produced using the organic-inorganic hybrid material of the present disclosure. The reason why the aggregation of QDs can be further suppressed can be presumed as follows. When the sum of abc is 1.04 or more, the compatibility between the organic chains on the surface of the QDs and the organic-inorganic hybrid material is improved. As a result, the dispersibility of the QDs is improved.
[0016] When the sum of abc is 1.04 or more, cracks are unlikely to occur in the organic-inorganic hybrid material. The reason why cracks are unlikely to occur can be presumed as follows. When the sum of abc is 1.04 or more, the organic-inorganic hybrid material does not have an excessively large amount of SiO skeletons, and the organic-inorganic hybrid material has high flexibility. As a result, cracks are unlikely to occur in the organic-inorganic hybrid material.
[0017] By making the sum of abc 1.49 or less, the amount of SiO skeleton in the organic-inorganic hybrid material is not excessively reduced, which makes the organic-inorganic hybrid material easier to cure.
[0018] The number average molecular weight of the organic-inorganic hybrid material of the present disclosure is, for example, not less than 300 and not more than 3000. The organic-inorganic hybrid material of the present disclosure is, for example, in the form of a liquid. The organic-inorganic hybrid material of the present disclosure may be in the form of, for example, a cured product. The cured product means a form in which, when an object and the organic-inorganic hybrid material are in contact with each other, the liquid that is a part of the organic-inorganic hybrid material does not adhere to the surface of the object.
[0019] The main chain of the polymer constituting the organic-inorganic hybrid material of the present disclosure is bonded by SiO bonds. Therefore, the organic-inorganic hybrid material of the present disclosure is excellent in transparency, heat resistance, and light resistance. Heat resistance means a property that transparency is not easily reduced even when heat is applied. Light resistance means a property that transparency is not easily reduced even when light is irradiated.
[0020] The organic-inorganic hybrid material of the present disclosure is R 1 , R 2 , R 3 By appropriately selecting one or more of these, it is possible to control properties such as the hardening property, the dispersibility of QDs, and the rate of cracking when hardening the composite material. The organic-inorganic hybrid material of the present disclosure can be produced, for example, by the following method: A solvent and an organosilane compound are mixed and heated at a first temperature to form a sol solution. At this time, the organosilane compound is polymerized by hydrolysis-dehydration-condensation.
[0021] The first temperature is, for example, a temperature of about 70° C. The organosilane compound used in the production may be a monomer or an oligomer. The first temperature is preferably higher than 60° C. When the first temperature is higher than 60° C., the viscosity of the organic-inorganic hybrid material is appropriately high, making the organic-inorganic hybrid material easy to handle. When the first temperature is higher than 60° C., the number average molecular weight of the organic-inorganic hybrid material is, for example, 300 or more.
[0022] The first temperature is preferably less than 80° C. When the first temperature is less than 80° C., the viscosity of the organic-inorganic hybrid material is appropriately low, making the organic-inorganic hybrid material easy to handle. When the first temperature is less than 80° C., the number average molecular weight of the organic-inorganic hybrid material is, for example, less than 3000.
[0023] Next, the sol solution is vacuum heated at a first temperature to evaporate the solvent, thereby obtaining a viscous liquid. The viscous liquid corresponds to the organic-inorganic hybrid material of the present disclosure. For example, the viscous liquid can be further heated at a second temperature to form a cured product. The cured product also corresponds to the organic-inorganic hybrid material of the present disclosure. The second temperature is, for example, a temperature of about 100°C.
[0024] 2.Composite materials The composite material of the present disclosure includes an organic-inorganic hybrid material of the present disclosure and QDs dispersed within the organic-inorganic hybrid material, for example, a matrix.
[0025] Examples of QDs include InP / ZnS core-shell quantum dots, CdSe / CdS core-shell quantum dots, CdSe / ZnS core-shell quantum dots, CdS / ZnS core-shell quantum dots, perovskite quantum dots, carbon-based quantum dots, WS2 and MoS2 quantum dots, CdTe core quantum dots, and PdS core quantum dots.
[0026] QD is, for example, a fluorescent material. The composite material of the present disclosure contains, for example, 0.1 parts by mass or more and 100 parts by mass or less of QD per 100 parts by mass of the organic-inorganic hybrid material.
[0027] The composite material of the present disclosure can be, for example, a material for an LED encapsulant, a lens, a sheet, a fiber, an ink, and the like. The composite material of the present disclosure can be produced, for example, by the following method. First, an organic-inorganic hybrid material in the form of a viscous liquid is produced by the above-mentioned method. Next, the organic-inorganic hybrid material in the form of a viscous liquid is mixed with QDs to obtain a composite material. Next, the composite material is heated at a second temperature and cured to obtain a cured product of the composite material.
[0028] 3. Working Example (1) Manufacturing of composite materials The composite materials of Examples 1 to 8 and Comparative Examples 1 to 6 were each produced by the following method. In the case of Examples 1 to 8, the raw materials shown in Table 1 were mixed and heated at 70°C for 3 hours to obtain a sol solution. In the case of Comparative Examples 1 to 6, the raw materials shown in Table 2 were mixed and heated at 70°C for 3 hours to obtain a sol solution.
[0029] [Table 1]
[0030] [Table 2]
[0031] In Tables 1 and 2, VTES is vinyltriethoxysilane. PhTES is phenyltriethoxysilane. DMDPhS is dimethoxydiphenylsilane. MTES is methyltriethoxysilane. DMDMS is dimethoxydimethylsilane. VTES, PhTES, DMDPhS, MTES, and DMDMS correspond to organosilane compounds, respectively. H2O, EtOH, and CH3COOH correspond to solvents.
[0032] The values in the "Heating temperature (°C)" row in Tables 1 and 2 indicate the temperature at which the raw materials were mixed and heated, and the temperature at which the sol solution was vacuum heated as described below. Next, for each of Examples 1 to 8 and Comparative Examples 1 to 6, the sol solution was vacuum heated at 70°C for 10 minutes to evaporate the solvent, thereby obtaining a viscous liquid. The viscous liquid corresponds to the organic-inorganic hybrid material of the present disclosure. The viscous liquid is a polymer formed by polymerization of an organic silane compound.
[0033] When VTES is included as a raw material, the organic-inorganic hybrid material has the following properties: 1 The organic-inorganic hybrid material contains a vinyl group derived from VTES as OX in formula (1). The organic-inorganic hybrid material contains an ethoxy group derived from VTES as OX in formula (1). The amount of vinyl and ethoxy groups derived from VTES in the organic-inorganic hybrid material is proportional to the amount of VTES contained in the raw material.
[0034] When PhTES is included as a raw material, the organic-inorganic hybrid material is 2 The organic-inorganic hybrid material contains a phenyl group derived from PhTES as OX in formula (1). The organic-inorganic hybrid material contains an ethoxy group derived from PhTES as OX in formula (1). The amount of phenyl groups and ethoxy groups derived from PhTES in the organic-inorganic hybrid material is proportional to the amount of PhTES contained in the raw material.
[0035] When DMDPhS is included as a raw material, the organic-inorganic hybrid material is 2 The organic-inorganic hybrid material contains a phenyl group derived from DMDPhS as OX in formula (1). The organic-inorganic hybrid material contains a methoxy group derived from DMDPhS as OX in formula (1). The amount of phenyl groups and methoxy groups derived from DMDPhS in the organic-inorganic hybrid material is proportional to the amount of DMDPhS contained in the raw material.
[0036] When MTES is included as a raw material, the organic-inorganic hybrid material is 3 The organic-inorganic hybrid material contains a methyl group derived from MTES as OX in formula (1). The organic-inorganic hybrid material contains an ethoxy group derived from MTES as OX in formula (1). The amount of methyl and ethoxy groups derived from MTES in the organic-inorganic hybrid material is proportional to the amount of MTES contained in the raw material.
[0037] When DMDMS is included as a raw material, the organic-inorganic hybrid material is 3 The organic-inorganic hybrid material contains a methyl group derived from DMDMS as OX in formula (1). The organic-inorganic hybrid material contains a methoxy group derived from DMDMS as OX in formula (1). The amount of methyl and methoxy groups derived from DMDMS in the organic-inorganic hybrid material is proportional to the amount of DMDMS contained in the raw material.
[0038] Next, the viscosity and number average molecular weight of the viscous liquid were measured for each of Examples 1 to 8 and Comparative Examples 1 to 6. The viscosity was measured by the following method. The measuring device was a "VISCOMETER TVE-25H" manufactured by Toki Sangyo Co., Ltd. The rotor was "1°34'×R24". The temperature during the measurement was 25° C. The rotor rotation speed during the measurement was 5 rpm. The viscosity was measured 2 minutes after the rotor started to rotate.
[0039] The method for measuring the number average molecular weight was as follows. The measuring device was a "Prominence-i LC-2030C LT" manufactured by Shimadzu Corporation. The column was a "Shodex KF-804L" manufactured by Showa Denko Co., Ltd. The solvent was tetrahydrofuran. The flow rate of the sample during the measurement was 1 ml / min. The temperature during the measurement was 40° C. The measurement results of the viscosity and number average molecular weight are shown in Tables 1 and 2.
[0040] Next, for each of Examples 1 to 8 and Comparative Examples 1 to 6, 666 μl of the QD solution was added to 0.01 g of the viscous liquid and mixed to produce a composite material. The QDs were uniformly dispersed in the composite material. The QD solution was of the perovskite type (Sigma-Aldrich, product number: 905062).
[0041] Next, for each of Examples 1 to 8 and Comparative Examples 1 to 6, 40 μl of the composite material was applied to a 1 cm square area on the surface of a glass plate. Next, the composite material was cured (hereinafter referred to as a curing treatment) by heating at 100° C. for 1 hour. In the curing treatment, crosslinking of the organic-inorganic hybrid material progressed further. As crosslinking progresses, d in formula (1) decreases and e increases.
[0042] The composite material after the hardening treatment was obtained by the above steps. a, b, c, and a+b+c in the composite material after the hardening treatment are shown in Tables 1 and 2. a+b+c means the sum of abc. (2) Evaluation of composite materials For each of Examples 1 to 8 and Comparative Examples 1 to 6, the composite materials after the curing treatment were evaluated as follows.
[0043] (2-1) Evaluation of hardening properties A spatula was placed in contact with the composite material after the curing treatment. If the liquid did not adhere to the spatula, the curability was judged to be good. If the liquid adhered to the spatula, the curability was judged to be poor. The evaluation results are shown in the "QD-added curing" row in Tables 1 and 2. "○" means that the curability is good. "×" means that the curability is poor. If the curability is good, the composite material after the curing treatment corresponds to a cured product.
[0044] (2-2) Evaluation of dispersibility The composite materials were observed using a Keyence BZ-X800 fluorescence microscope and a "TRITC" filter. When no fluorescence with a wavelength of 570-640 nm was observed, the dispersibility was evaluated as good. When fluorescence with a wavelength of 570-640 nm was observed, the dispersibility was evaluated as poor. The evaluation results are shown in the "Dispersibility" row in Tables 1 and 2. "○" means that the dispersibility is good. "×" means that the dispersibility is poor.
[0045] The QDs contained in the composite material fluoresce at wavelengths of 495 to 565 nm. When QDs aggregate, the wavelength of the fluorescence shifts to the longer wavelength side. Therefore, when fluorescence is observed at wavelengths of 570 to 640 nm, the QDs are aggregated and the dispersion is poor.
[0046] (2-3) Crack evaluation The composite material was observed using a microscope, and the number of cracks within a 200 μm square was counted. When the number of cracks was between 0 and 4, it was judged that there were few cracks. When the number of cracks was 5 or more, it was judged that there were many cracks. The judgment results are shown in the "Crack occurrence" row in Tables 1 and 2. "○" means that there were few cracks. "×" means that there were many cracks.
[0047] (2-4) Other characteristics The organic-inorganic hybrid materials of Examples 1 to 8 are excellent in transparency, heat resistance, and light resistance. The organic-inorganic hybrid materials of Examples 1 to 8 are thermosetting organic-inorganic hybrid materials. Therefore, the organic-inorganic hybrid materials of Examples 1 to 8 are easy to handle and have moldability. 4. Other embodiments Although the embodiments of the present disclosure have been described above, the present disclosure is not limited to the above-described embodiments and can be implemented in various modified forms.
[0048] (1) The organic-inorganic hybrid material may be UV-curable. (2) The organic-inorganic hybrid material may be cured without being mixed with QDs. (3) The composite material may further contain other components in addition to the organic-inorganic hybrid material and QDs.
[0049] (4) The function of one component in each of the above embodiments may be shared by multiple components, or the functions of multiple components may be performed by one component. Also, part of the configuration of each of the above embodiments may be omitted. Also, at least part of the configuration of each of the above embodiments may be added to or substituted for the configuration of another of the above embodiments.
[0050] (5) In addition to the organic-inorganic hybrid material described above, the present disclosure can be realized in various forms, such as a product having the organic-inorganic hybrid material as a component, a method for producing an organic-inorganic hybrid material, and a method for producing a composite material.
Claims
1. An organic-inorganic hybrid material which is a cured product of a material represented by formula (1), which is an average composition formula. Formula (1) SiR 1 a R 2 b R 3 c (OX) d (O 1/2 ) e (R in formula (1) 1 is at least one selected from the group consisting of a vinyl group, an acrylic group, a methacrylic group, and an allyl group. 2 is at least one selected from the group consisting of a phenyl group, a 4-methoxyphenyl group, and a benzyl group. 3 is at least one selected from the group consisting of a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a cyclopentyl group, a cyclohexyl group, a hexyl group, an n-octyl group, an isooctyl group, a decyl group, a dodecyl group, a hexadecyl group, an n-octadecyl group, and an octadecyl group. X in formula (1) is a hydrogen atom or an alkyl group. O in formula (1) 1/2 is a bridging oxygen. In formula (1), a is a numerical value of 0.04 or more and 0.26 or less. In formula (1), b is a numerical value of 0.13 or more. In formula (1), c is a numerical value of 0.09 or more. In formula (1), d is a numerical value of 0 or more. In formula (1), e is a numerical value of 0 or more. The sum of a, b, and c is a numerical value of 1.04 or more and 1.49 or less. The sum of a, b, c, d, and e is 4.)
2. The organic-inorganic hybrid material according to claim 1; Quantum dots dispersed within the organic-inorganic hybrid material; Composite material comprising:
Citation Information
Patent Citations
Production method of inorganic fine particle dispersion, inorganic fine particle dispersion, coating film, and laminate
JP2015217359A
Manufacturing method of hydrophobized inorganic nanoparticle and inorganic nanoparticle dispersion
JP2017210385A
Silicon-containing curable composition, cured product of the silicon-containing curable composition and lead frame substrate formed of the silicon-containing curable composition
WO2011155459A1
Curable resin composition, cured product of same and semiconductor device
WO2018016372A1
Curable silicone composition and cured product thereof
WO2019177969A1